Penggunaan Abu Tempurung Kelapa Dan Kapur Hidrolis Sebagai Bahan Pengganti Semen Pada Mortar Geopolimer - Beni Rizky Alfarisi; Anita Intan Nura Diana (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2024)
This research aims to find out how to use coconut shell ash and hydraulic lime as a substitute for cement in geopolymer mortar. Geopolymer mortar is a type of mortar that does not use cement at all. Geopolymer is the answer to replacing cement, because cement production has a bad impact, namely that it can damage the environment. CO2 emission gas is not only produced in the process of making cement, but CO2 emission gas is produced when it is used in concrete mixtures. This research method is by comparing precursors, the ratio of precursor to activator. The precursors used in this research were coconut shell ash and hydraulic lime, while the alkali activators used were Sodium Hydroxide (NaOH) and Sodium Silica (Na2SiO3). The use of variations in coconut shell ash precursor with hydraulic lime is 50:50, 60:40, 70:30. Alkali variation of NaOH activator with Na2SiO3 is 50:50, while variation of precursor with activator is 70:30 and 80:20. The treatment method used in this research was in the oven at 60°C and left at room temperature.